Chlorophyll fluorescence and spectral reflection of leaf as stress indicator in seedling - Shamsul, Bin Bojeng (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The physiological qualities ofthe seedlings are important factors for a successful field planting. Much interest in the early assessment of growth stress has been generated recently by the spreading acceptance of the precision agriculture running concept. Ground-based spectral imaging devices offer an important supplement to satellite imagery. These hand-held sensors allows rapid, inexpensive measurements that are least affected by atmospheric variables. The study aim at evaluating the spectral response of seedling and their observed physiological changes subjected to drought and nutrient stress. Experiments were conducted with two month-old Acacia mangium seedlings grown on a nursery 70th water and fertilization regimes were applied to the seedlings where variables such as chlorophyll content, leaf moist\"e content and their respective spectral response were recorded for a one week period. Distinct physiological changes of seedlirrgs under nutrient and water stress are reflected in bio-indicators such as the leaf chlorophyll content and photochemical efficiency. Changes in the leaf anatomical characteristic were more pronounced due to loss of water. These physiological changes are spectrally distinct at the visible (400700nm) and near infra-red (700-1200nm) spectral regions, which provided an opportunity to utilize these wavelength in remotely sensed instrument by extracting features related to such changes. Results shows the potential for adopting physiological indicators as early indicators of plant stress and with the use of high fidel ity sensing instruments, these bio-indicators provide more effective tools in ensuring good nursery practices.